Update on Cryptosporidium spp.: highlights from the Seventh International Giardia and Cryptosporidium Conference - Widmer, Giovanni; Carmena, David; Kváč, Martin; Chalmers, Rachel M; Kissinger, Jessica C; Xiao, Lihua; Sateriale, Adam; Striepen, Boris; Laurent, Fabrice; Lacroix-Lamandé, Sonia; Gargala, Gilles; Favennec, Loïc (Parasite (Paris, France), 2020)
While cryptosporidiosis is recognized as being among the most common causes of human parasitic diarrhea in the world, there is currently limited knowledge on Cryptosporidium infection mechanisms, incomplete codification of diagnostic methods, and a need for additional therapeutic options. In response, the Seventh International Giardia and Cryptosporidium Conference (IGCC 2019) was hosted from 23 to 26 June 2019, at the Rouen Normandy University, France. This trusted event brought together an international delegation of researchers to synthesize recent advances and identify key research questions and knowledge gaps. The program of the interdisciplinary conference included all aspects of host-parasite relationships from basic research to applications to human and veterinary medicine, and environmental issues associated with waterborne parasites and their epidemiological consequences. In relation to Cryptosporidium and cryptosporidiosis, the primary research areas for which novel findings and the most impressive communications were presented and discussed included: Cryptosporidium in environmental waters, seafood, and fresh produce; Animal epidemiology; Human cryptosporidiosis and epidemiology; Genomes and genomic evolution encompassing: Comparative genomics of Cryptosporidium spp., Genomic insights into biology, Acquiring and utilizing genome sequences, Genetic manipulation; Host-parasite interaction (immunology, microbiome); and Diagnosis and treatment. High quality presentations discussed at the conference reflected decisive progress and identified new opportunities that will engage investigators and funding agencies to spur future research in a "one health" approach to improve basic knowledge and the clinical and public health management of zoonotic cryptosporidiosis.
Keywords: průjem; Giardia; feces; kongresy jako téma; Humans; Cryptosporidiosis; kryptosporidióza; giardiáza; Congresses as Topic; Diarrhea; One Health; Cryptosporidium; lidé; Genotype; Epidemiology; zvířata; Giardiasis; Feces; Francie; France; genotyp; Animals; Genomics